A protocol for the large‐scale analysis of reefs using Structure from Motion photogrammetry - Bayley, Daniel T. I.; Mogg, Andrew O. M.; Ellison, Aaron (Methods in ecology and evolution, 2020)
Substrate complexity is an essential metric of reef health and a strong predictor of several ecological processes connected to the reef, including disturbance, resilience, and associated community abundance and diversity. Underwater Structure from Motion (SfM) photogrammetry has been growing rapidly in use over the last 5 years due to advances in computing power, reduced costs of underwater digital cameras and a push for reproducible data. This has led to the adaptation of an originally terrestrial survey technique into the marine realm, which can now be applied at the habitat scale. This technique allows researchers to make detailed 3D reconstructions of reef surfaces for morphometric analysis of reef physical structure and perform large‐scale image‐mosaic mapping. SfM is useful for both reef‐scale and colony‐scale assessments, where visual or acoustic methods are impractical or not sufficiently detailed. Here we provide a protocol for the collection, analysis and display of 3D reef data, focussing on large‐scale habitat assessments of coral reefs using primarily open‐source software. We further suggest applications for other underwater environments and scales of assessment, and hope this standardized protocol will help researchers apply this technology and inspire new avenues of ecological research.